Aspek Hukum Perjanjian Pinjaman Online Ditinjau dari Kuhperdata dan UU ITE - Citimerli Simarmata; Evan Federico Siregar (Syntax Literate, 2023)
Online-based borrowing loans and electronic transactions aim to help the community's economic development, especially MSMEs. Information and electronic transactions are the collections of electronic data, both social media accounts and mobile phone numbers, in the form of user identities legally identified. The truth is kept confidential for the safety and convenience of electronic media users, especially electronic transactions and legal arrangements for information and electronic transactions. Indonesia has particular regulations or UU, namely cyber law (UU ITE) No. 11/2008 and Kominfo Regulation No. 20/2016, for personal data and electronic systems protection. Fintech lending (loans online) is done legally and witnessed by PT. Digital Indonesia. It has been supervised and subjected to the laws of the Republic of Indonesia. The provision of volunteered authority finance services lends legal funds and uses the funds legally. If it is found to be illegal, it is entitled to report it and take responsibility for user actions. The service provider settings of financial services authority No.77/POJK.01/2016, an engagement born of an agreement led to the validity of an agreement article 1320 of the Civil Code (KUHPerdata). The research data was through normative juridical research methods from books, laws, legal dictionaries. Legal protection for debtors’default was within Article 4 of the Law on consumer legal protection No. 8/1999 part first. And creditors get legal assurance if the debtor defaults in Article 51 of Law No. 5/1960 and Law No. 4/1996. Also, creditors may give sanctions to debtors for default in Article 20 paragraph (1) of the Law on Rights dependents.